Study of Seasonal Trends of Suicidal Deaths in Gulbahga Region of Karnataka (Indian Internet Journal of Forensic Medicine and Toxicology, 2010)
Suicide which is a common cause of unnatural deaths continues to be a major problem, a retrospective and prospective study of sociodemographic profile, causes of suicide, method of suicide and various trends of suicidal distribution in Gulbarga region was conducted over a period of five years from 1st January 2000 to 31st December 2004 using the data from hospital admission papers, police records, postmortem reports, suicide notes if any and history from the relatives & friends accompanying the deceased.
Keywords: Suicide; seasonal trends; chronic illness; Poisoning